Immobilization of Xylanase on ZnO nanoparticles obtained by green synthesis from Eupatorium cannabinum L. and its application in enrichment of fruit juices - Pekdemir, Sibel Selcuk; Baskar, Busra; Tas, Recep; Ulu, Ahmet; Pekdemir, Mustafa Ersin; Ates, Burhan (Elsevier, 2024)
Juice production is one of the main components of the nutritional food industry. Therefore, improving fruit juice quality and preventing the formation of negative by-products is important for human health. The role of environmentally friendly, safe and economically more affordable green nanocarriers in improving the quality of fruit juice is increasing day by day. For this purpose, zinc oxide nanoparticles (ZnONPs) were prepared from the aqueous extract of the Eupatorium cannabinum L. using the green synthesis method. After immobilization, structural and morphological characterizations of the prepared ZnONPs and xylanase (Xyl)@ZnONPs were carried out, which confirmed that both the synthesis of ZnONPs and the immobilization of Xyl enzyme on ZnONPs were successfully carried out. The biochemical parameters of Xyl@ZnONPs such as optimum pH and temperature, kinetic parameters, thermal stability, reusability, and storage stability were investigated and compared with free Xyl. After immobilization, the optimum pH of free Xyl shifted from 5.0 to an alkaline pH of 8.0, while no change in the optimum temperature (70 degree celsius) was observed for both enzymes. While the activation energy of free Xyl was 5.56 kJ/mol, it was found to be 7.27 kJ/mol for Xyl@ZnONPs. Xyl@ZnONPs outperformed free Xyl due to its long-term storage stability and reusability. Moreover, Xyl@ZnONPs retained 50 % of its activity after 5 reuses and 87 % of its activity after 4 weeks of storage at room temperature. In addition, a decrease in Km value and an increase in Vmax value were observed after immobilization, which means the increased catalytic activity of the Xyl@ZnONPs. As a result of re-using Xyl@ZnONPs in orange juice for 6 cycles, clarification yield of 66.43 % was obtained under optimized conditions. Overall, this study prepared a suitable, environmentally friendly, and robust carrier support for Xyl immobilization and developed a biocatalyst that will provide high performance in the industrial field.
Keywords: Green synthesis; ZnO nanoparticles; Xylanase; Enzyme immobilization; Fruit juice clarification